Advances and challenges of integrated thermal management technologies for pure electric vehicles. (August 2021) - Liang, Kunfeng; Wang, Moran; Gao, Chunyan; Dong, Bin; Feng, Changzhen; Zhou, Xun; Liu, Jing
Abstract: Zero-emission pure electric vehicles (PEVs) have been progressively developed towards scale production as passenger cars. However, the power, economy, driving range, and other indicators are seriously restricted by onboard batteries. In freezing winter and sultry summer, these problems are greatly aggravated by the energy versus temperature characteristics of the batteries and the turning on of air conditioning (AC). Against this background, three key issues related to thermal management in the development of PEVs: battery thermal management (BTM) technology, cabin thermal management technology (air conditioning system), and integrated thermal management (ITM) technology are proposed. The corresponding advances which are in the embryonic stage are briefly summarized in this paper. By analyzing the cross-functional parts of two auxiliary systems with similar thermal management roles, it is indicated that ITM is the necessary and inevitable way to develop PEVs. ITM can realize the lightweight of PEVs and make up for the shortcomings of each subsystem.